Study on the constitutive model and thermal deformation behavior of Incoloy825/P110 bimetallic composite material - Hao Liu; Qiang Li; Hailian Gui; Chen Zhang; Sha Li; Leifeng Tuo; Jianxun Chen; Pengyue Zhang; Chunlei Shen (Scientific Reports)
Abstract To further investigate the properties of Incoloy825/P110 bimetallic composite seamless pipes, thermal deformation analysis was conducted on their billets. The thermal deformation and dynamic recrystallization (DRX) behavior of Incoloy825/P110 bimetallic composite materials were studied through hot compression tests at deformation temperatures (850–1150 °C) and strain rates (0.01–10 s−1). A constitutive relationship was established, and compensation and correction were made based on the differences in materials corresponding to different strain states. The hot processing map was established based on the thermal deformation behavior of bimetallic materials. In addition, the evolution of microstructure was also studied to verify the feasibility of the established hot processing map. The results show that the strain compensated Arrhenius can accurately predict the flow stress. By analyzing the microstructure using EBSD, it can be found that DRX behavior has a significant impact on the thermal processing properties of composite materials. This study provides an important theoretical basis for the production of Incoloy825/P110 bimetallic composite seamless pipes in the future.